Processor description languages applications and methodologies - Mishra, Prabhat, 1973-; Dutt, Nikil (Amsterdam ; Boston : Morgan Kaufmann Publishers/Elsevier, 2008)
Efficient design of embedded processors plays a critical role in embedded systems design. Processor description languages and their associated specification, exploration and rapid prototyping methodologies are used to find the best possible design for a given set of applications under various design constraints, such as area, power and performance. This book is the first, comprehensive survey of modern architecture description languages and will be an invaluable reference for embedded system architects, designers, developers, and validation engineers. Readers will see that the use of particular architecture description languages will lead to productivity gains in designing particular (application-specific) types of embedded processors. * Comprehensive coverage of all modern architecture description languages ... use the right ADL to design your processor to fit your application; * Most up-to-date information available about each architecture description language from the developers ... save time chasing down reliable documentation; * Describes how each architecture desccription language enables key design automation tasks, such as simulation, synthesis and testing ... fit the ADL to your design cycle.
Introduction: Motivation, Software ADLs, Hardware ADLs; Classification? content-based/activity based; Behavioral ADLs: nML; ISDL; Valen-C; CSDL; Structural ADLs: MIMOLA; UDL/I; Mixed ADLs: EXPRESSION; LISA; Flexware; TDL; HMDES; MADL; ADL-driven Methodlogies: Simulation; Synthesis; Validation/Verification; System ADLS: Case Studies using SpecC, SystemC and UML; Conclusion.
Includes bibliographical references and index.
Keywords: Embedded computer systems; Electronic books